Multidisciplinary open access repositories [electronic resource] (Unesco, 2017)
The Global Open Access Portal (GOAP) funded by the Governments of Colombia, Denmark, Norway, and the United States Department of State, presents a current snapshot of the status of Open Access (OA) to scientific information in 158 countries worldwide. For countries that have been more successful in implementing Open Access, the portal highlights critical success factors and aspects of the enabling environment. For countries and regions that are still in the early stages of Open Access development, the portal identifies key players, potential barriers and opportunities. The Global Open Access Portal is designed to provide necessary information for policy-makers to: Learn about the global Open Access environment; View their country?s status; and Understand where and why Open Access has been most successful.